Action-Depicting Gestures and Morphosyntax: The Function of Gesture-Speech Alignment in the Conversational Turn - Urbanik, Paweł; Svennevig, Jan (Frontiers in Psychology, 2021)
The current study examines the role of action-depicting gestures in conversational turns by focusing on their semantic characteristics and temporal position in relation to their verbal affiliates (action verbs or more complex verb phrases). The data are video recordings of naturally occurring interactions in multilingual construction sites in Norway. The analysis distinguishes two modes of action depiction: generic depictions, which represent the action as a general type, and contextualized depictions, which in addition include deictic references to the spatio-material environment or iconic representations of the specific manner of action performance. These two modes typically occupy different positions in the turn. Generic depictions are mostly initiated before the verbalization of the action or are synchronized with it, while contextualized depictions mostly start simultaneously with the verbalization and extend beyond the verb phrase or the turn. The pre-positioned and synchronized generic gestures are shown to serve as a practice for facilitating recognition of the verbalized action and may be temporally manipulated in order to pre-empt understanding problems in the face of reduced common linguistic resources. The post-positioned contextualized depictions serve instead to add specifying information about aspects of the action referred to and thereby to complement or supplement the meaning of the verb phrase, securing understanding of action specifics. The study contributes to research on gesture-speech synchrony by demonstrating how variation in the alignment of action depiction and syntax is used to direct the recipient’s attention towards different interactional goals.